Evaluación del comportamiento en poscosecha de la fresa (Fragaria vesca), con tres recubrimientos comestibles a tres tiempos de inmersión, en la provincia de Cotopaxi cantón Latacunga 2020. - Iza Iza, Danny Paul (2020)
This draft research titled "Evaluation of post-cut strawberry behaviour (Fragaria vesca), with three edible coatings at three times of immersion, in the province of Cotopaxi canton Latacunga 2020." It was carried out in the province of Cotopaxi parish Eloy Alfaro campus Salache in the post-harvest laboratory of the career of Agronomic Engineering, where strawberries of the variety (Diamond) with three edible coatings were tested: honey, lemon juice and lemon juice with honey, three immersion times, 1, 2 and 3 minutes. With nine treatments and three repetitions. The indicators that were evaluated were: Weight (p=m.g), Firmness (lbfcas x cm) Soluble solids (Brix) and pH (acid – alkaline), the results of the edible coating were RC1 honey occupies the first range with an average of 0.49; 0.33 g on days 3 and 5 occupying a range A of the variable firmness, as it also occupies the first range with an average of 4.93 g on day 7 occupying a range A of the variable pH. The immersion time was T3 3 minutes occupies the first range with averages of 2; 1.57 on days 4 and 7 occupying A range of A of the variable weight. As well as T2, it is the first place 2 minutes with averages of 0.29; 0.32 and 0.19 On day 1, 6, 9 occupying A range of A of the variable firmness, T1 also ranks first 1 minute with an average of 4.21 on day 5 occupying A range of A of the variable pH. . Treatment in edible coating and immersion time interactions was T3 RC2 with an average of 3.1 occupying A range of to the weight variable, Also in the first place the RC2 T1 with an average of 4.66 occupies A range of to the pH variable being the best in treatments.